The Effect of Nesfatin-1 Levels on Paroxysmal Supraventricular Tachycardia - Celik, Ahmet; Gurger, Mehtap; Can, Cagdas; Balin, Mehmet; Gul, Evrim; Kobat, Mehmet Ali; Aydin, Suleyman (Elsevier Science Inc, 2013)
[Abstract Not Available]
29th Turkish Cardiology Congress of the Turkish-Society-of-Cardiology (TSC) with International Participation -- OCT 26-29, 2013 -- Antalya, TURKEY